1984
DOI: 10.1002/pssb.2221220137
|View full text |Cite
|
Sign up to set email alerts
|

The Simulation and Interpretation of the EPR Powder Spectra of Gd3+‐Doped LaAlO3

Abstract: The EPR powder spectra of Gd3+ doped LaA10, are simulated for a number of temperatures between 4 and 800 K by means of the usual spin-Hamiltonian. Values are found for the zero field splitting parameters B(n, 0) only, which agree with single crystal measurements. For an accurate simulation of the axial powder spectra a variable linewidth has to be introduced, because an inhomogeneous broadening of the resonances in the zy plane is observed. This broadening is successfully described by a variable B(2, 2) parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…They confirmed the validity of the analysis by comparing with single-crystal EPR studies. Koopmans et al also demonstrated a parametrization procedure by the combined use of Abraham's approach and computer simulation based on numerical diagonalization of the spin Hamiltonian . On the other hand, we reported another approach using the hybrid-eigenfield method instead of the numerical diagonalization …”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…They confirmed the validity of the analysis by comparing with single-crystal EPR studies. Koopmans et al also demonstrated a parametrization procedure by the combined use of Abraham's approach and computer simulation based on numerical diagonalization of the spin Hamiltonian . On the other hand, we reported another approach using the hybrid-eigenfield method instead of the numerical diagonalization …”
Section: Introductionmentioning
confidence: 77%
“…Koopmans et al also demonstrated a parametrization procedure by the combined use of Abraham's approach and computer simulation based on numerical diagonalization of the spin Hamiltonian. 20 On the other hand, we reported another approach using the hybrideigenfield method instead of the numerical diagonalization. 21 In this work, the approach was extended by considering all fourth-order terms, and it can be addressed for other S ) 7/2 systems.…”
Section: Introductionmentioning
confidence: 99%